Chile : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper reviews the benefits and costs of reserves for Chile, with emphasis on standard methodologies for assessing reserve adequacy. It reports an empirical methodology that analyzes simultaneously key explanatory variables behind a country's level of reserves. The paper previews mechanisms that could supplement a country's liquidity needs in times of stress. This paper also describes the instruments available for hedging foreign exchange risk, the demand and supply of foreign exchange hedging in the onshore market, and assesses foreign exchange exposure in different industrial sectors using factor analysis.